Tensile Testing Assay for the Measurement of Tissue Stiffness in Arabidopsis Inflorescence Stem - kouki yoshida; shingo sakamoto; Nobutaka Mitsuda (Bio-Protocol, 2019)
Lignocellulosic biomass is a versatile renewable resource for fuels, buildings, crafts, and biomaterials. Strategies of molecularly designing lignocellulose for industrial application has been developed by the discoveries of novel genes after the screenings of various mutants and transformed lines of Arabidopsis whose cell walls could be modified in the inflorescence stem, a model woody tissue. The mechanical properties are used as a quantitative index for the chemorehological behavior of the genetically modified cell wall in the tissue. This parameter can be measured with tensile or bending tests of tissue explants, the vibration analysis of tissue behavior or using atomic force microscopy to probe the tissue surface. Here, we describe in detail the procedure to determine the stiffness of methanol-fixed, rehydrated and pronase-treated inflorescence explants with a tensile testing machine based on classical methods for the determination of cell wall extensibility.